2020
DOI: 10.31234/osf.io/28tnw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Link Between Ego-resiliency, Social Support, SARS-CoV-2 Anxiety and Trauma Effects. Polish Adaptation of the Coronavirus Anxiety Scale

Abstract: Reports to date have shown that the SARS-CoV-2 pandemic may have a negative impact on individuals’ mental health. The purpose of this study was to assess the relation between ego-resiliency, social support, coronavirus anxiety and trauma effects. The study employed the Polish adaptation of the Coronavirus Anxiety Scale (CAS). It involved 515 individuals aged 18–78. The Polish version of CAS revealed satisfactory psychometric properties (α = .86). Structural equation modelling indicat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
13
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 9 publications
7
13
0
5
Order By: Relevance
“…However, the perception of more social support can make them feel cared for, understood, and valued by others, which can strengthen one's self-efficacy in coping with the uncertainty of the future (Casale and Flett, 2020). Confirming and extending previous findings on the benefits of social support in disasters (Arnberg et al, 2012;Gabert-Quillen et al, 2012;Guilaran et al, 2018;Skalski et al, 2020), findings from the present study demonstrated the protective role of social support for lonely people across different stages of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…However, the perception of more social support can make them feel cared for, understood, and valued by others, which can strengthen one's self-efficacy in coping with the uncertainty of the future (Casale and Flett, 2020). Confirming and extending previous findings on the benefits of social support in disasters (Arnberg et al, 2012;Gabert-Quillen et al, 2012;Guilaran et al, 2018;Skalski et al, 2020), findings from the present study demonstrated the protective role of social support for lonely people across different stages of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, among the different symptoms of coronavirus anxiety, 'tonic immobility' and 'sleep disturbance' were reported to be the most pronounced symptoms. This result is similar to those of a study involving the general population in Poland in which these items obtained the highest means (Skalski, Uram, Dobrakowski, & Kwiatkowska, 2020). In addition, in a study by Shevlin et al 2020 while tonic immobility occurs involuntarily as a result of heightened fear and typically occurs in individuals who experience highly traumatic situations (Möller, Söndergaard, & Helström, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…De Buck (2020), maximizing resilience in HCWs during the COVID-19 crisis was seen as vital to helping them safeguard their mental and psychological health and well-being. This pattern of influence was similar to that found in a general population, in which personal resilience and social support contributed significantly to reducing the severity of anxiety associated with the novel coronavirus (Skalski et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…The reason behind this may be attributed to the stability of the health status of this age group compared to the age group 1-10 years in which the family is more worried because it is a recent incident the family witnessed, because the health status of the children of these families is still a source of worry, which causes a decrease in the psychological and social adaptation of the families of this group. Previous investigations proved the existence of such an impact, not only on the disabled person but also on the family in general (Skalski et al, 2020;Tummers et al, 2020;Stankovska et al, 2020;Brooks et al, 2020).…”
Section: mentioning
confidence: 96%